SANG KRISTUS DALAM PUISI INDONESIA MODERN - Yoseph Yapi Taum (Sintesis, 2016)
SAIndonesia is a country with Muslims majority population in this world. Before 1970, Teeuw notedthat the figure of Christ was not known publically for Indonesians. However, after 1970, I observethat the image of The Christ get more common for Indonesian, as it was shown at the works ofliterature. In this paper, I show that the Christ was experienced by at least 10 Indonesian poets on25 poetries. They are not only Christians but also Muslims. On their works, we will learn 5 dominantthemes, i.e: 1) Christ as the Savior of all human; 2) Christ belongs to a certain community; 3).Christ makes the sinners repentance; 4) People doubt of Christ holiness; and 5) Christ is a cruelJudge.